New features in systematics of low-spin states in even 106−120Cd - Kumpulainen, Jaana (1990)
Low-lying low-spin collective states in even 106,108,110,112,116Cd were investigated by means of in-beam and off-beam γ-ray and conversion-electron spectroscopy. New spin assignments and decay branching ratios for the levels in 106Cd, 108Cd, 110Cd and 112Cd were obtained. The present results essentially complement the level systematics from 106Cd to 120Cd. From the new data, it is inferred that two sets of low-lying 0+ states having different excitation characteristics cross between 114Cd and 116Cd. No such crossing is observed on the neutron-deficient side. One of these sets appears to have features of both intruder and two-quadrupole-phonon states.